Taxonomy of high-latitude Goniasteridae (Subantarctic & Antarctic): one new genus, and three new species with an overview and key to taxa - Mah, Christopher L. (Zenodo, 2011)
Mah, Christopher L. (2011): Taxonomy of high-latitude Goniasteridae (Subantarctic & Antarctic): one new genus, and three new species with an overview and key to taxa. Zootaxa 2759: 1-48, DOI:10.5281/zenodo.276783